Processus de jugement d’évaluation des compétences professionnelles en contexte de stage en emploi : quand les stagiaires sont également des collègues - Desmeules, Amélie; Wentzel, Bernard; Hamel, Christine (Canadian Journal of Education/Revue canadienne de l’éducation, 2025)
In the context of a shortage of qualified teaching staff (Dupriez et al., 2023), paid internships are gaining in popularity, but they are forcing the pre-service training and work environments to rethink their collaboration. With this in mind, we developed a paid internship program as part of a research project conducted in partnership with a school board. The aim of the study is to document the issues perceived by the trainers involved in the assessment of skills in the context of paid internships regarding their assessment judgement process. As paid internships opportunities are recent in elementary and secondary teacher training programs, our article will contribute to the development of knowledge about their impact, which is currently scarcely documented (CSÉ, 2023). Therefore, we conducted a content analysis (Krippendorff, 2013) based on transcribed semi-directed interviews in order to identify emerging and recurring themes regarding the perceptions of the trainers (n = 8) pertaining to issues perceived in their evaluation judgement process in this context. Our results highlight several issues arising from the status of colleague, involving a change in the relationships between individuals involved, on the characteristics of the process of assessing the professional skills of trainees. Our proposal points to a need to clarify the roles of trainers in the context of paid internships, particularly with regard to evaluation.